When is transition over? - Brown, Annette N., 1966- (W.E. Upjohn Institute for Employment Research, 1999)
Contains six lectures which discuss criteria for determining the end of the transition process. These include changes in the characteristics of the economic system, outcomes of the transition process, and institutional reforms.